Implementation of clinical pharmacist recommendations and services at a University Hospital in Yemen - Kubas, Mohammed A.; Halboup, Abdulsalam M. (Springer Nature, 2020)
Background: Studies have revealed that the inclusion of a clinical pharmacist as a member in multidisciplinary medical team has been associated with improved medication use, reduced adverse drug reaction, reduced cost of treatment, and improved health outcomes. Objective: The objectives of this study were to evaluate the implementation of clinical pharmacy recommendations and services, the acceptance rate by the physicians, and the anticipated outcomes of the recommendations at a hospital in Yemen. Methods: Different units of the University of Science and Technology Hospital, Sanaa were included in this study. All the recommendations and services provided by the clinical pharmacist during daily activities were documented between June 2013 and November 2015. The provided recommendations were classified based on the type, acceptance rate, and the anticipated outcomes. Main outcome measure Type and quality of clinical pharmacists recommendations, anticipated impact of the recommendations on health outcomes, and their acceptance rate. Results: Throughout the study period, a total of 957 patients in different hospital units were visited and provided with a total of 3307 interventions and services. The most frequent types of clinical pharmacists interventions were drug discontinuation (23.6%, n?=?782), inappropriate dose interval or time (n?=?735, 22.2%), and add medication (18.9%, n?=?626). Overall, 61.8% (n?=?2044) of the provided recommendations were accepted by the physicians. The most anticipated outcomes were improved the effectiveness of therapy (45.1%, n?=?1909), avoid adverse drug reactions (29%, n?=?1228), and decrease the cost of medications (18.8%, n?=?797). Conclusion: Clinical pharmacists recommendations resulted in improving drug therapy and decreasing adverse effects for inpatients at the University of Science and Technology Hospital. This suggests that the implementation of clinical pharmacy services is essential and has a positive outcome on patient care.